Motion Graphic Iklan Layanan Masyarakat Edukasi Tata Tertib Rambu Lalu Lintas - Muhammad Ilham; Muchamad Fajri Amirul Nasrullah (Politeknik Negeri Batam, 2021)
Public service advertisements are advertisements that present social messages that aim to raise public awareness of a number of problems they must face, namely conditions that can threaten harmony and public life. Lack of awareness by motorcyclists often has fatal consequences for themselves and even others. In fact, many of the motorcyclists violate established regulations which aim to control traffic on the highway. So a research was made to produce motion graphic video public service advertisements regarding traffic signs education using the quantitative research method with the Vaughan settlement method. And on the results of the analysis carried out, it can be seen that the results are at the level of effectiveness based on the Likert scale interval for the expert, the predicate is